Acute Exacerbations in COPD and Their Control with Oral Immunization with Non-Typeable Haemophilus Influenzae - Clancy, Robert; Dunkley, Margaret (Frontiers in Immunology, 2011)
Chronic obstructive pulmonary disease (COPD) a term based on the demonstration of irreversible airways obstruction, introduced to unify a range of chronic progressive diseases of the airways consequent upon inhalation of toxins. While disease is initiated and progressed by inhaled toxins, an additional pathway of damage has emerged, with particular relevance to acute exacerbations. Exacerbations of disease due to an increase in the level of intra-bronchial inflammation have taken on a new significance as their role in determining both acute and chronic outcomes is better understood. This ‘second pathway’ of disease is a consequence of bacterial colonisation of damaged airways. Although bacteria have been linked to acute episodes in COPD over 50 years, only recently has quality data on antibiotic usage and the detection of ‘exacerbation isolates’ of non-typeable Haemophilus influenzae (NTHi) provided strong argument in support of a pathogenic role. Yet a poor correlation between detection of colonising bacteria and clinical status remained a concern in attempts to explain a role for bacteria in a classical infection model. This presentation discusses a hypothesis that acute exacerbations reflect a T-cell dependent hypersensitivity response to colonising bacteria, with IL-17 dependent accumulation of neutrophils within the bronchus, as the main outcome measure. Critical protection against exacerbations following oral administration of NTHi, an immunotherapy that drives a TH17 Tcell response from Peyer’s patches, reduces the load of intrabronchial bacteria while preventing access of inhaled bacteria into small airways. Immunotherapy augments a physiological ‘loop’ based on aspiration of bronchus content into the gut. A second ‘hypersensitivity’ mechanism may cause bronchospasm – in both COPD and treatment-resistant asthma – due to specific IgE antibody directed against colonising bacteria, as oral NTHi abrogates wheeze in subjects with recurrent ‘wheezy bronchitis’.